New dammarane triterpenoid saponins from the leaves of Cyclocarya paliurus. Issue 11 (2nd November 2018) - Wang, Yi-Rui; Cui, Bao-Song; Han, Shao-Wei; Li, Shuai
Abstract: Three new dammarane triterpenoid saponins, cyclocariosides O-Q (1–3 ), were isolated from the ethanolic extracts of the leaves of Cyclocarya paliurus . The structures of these compounds were elucidated by spectroscopic methods. Abstract :